KEARIFAN LOKAL PEMANFAATAN TUMBUHAN OBATDALAM OLEH MASYARAKAT DI SEKITAR TAMAN NASIONAL AKETAJAWE LOLOBATA, PROVINSI MALUKU UTARA - Lis Nurrani (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Utilization of  forest plants in traditional medicine by community around the Aketajawe Lolobata National Park (ALNP) is  one of  local wisdom that must be maintained. The aim of  this research is to enrich the bioecology data so it can be used as a reference in forest management based on community welfare and environmental sustainability. This research was conducted to assess the utilization of  medicinal plants by the community in the traditional zones of  AL . The method used were in-depth interview (questionnaire), field NP  surveys, and phytochemical analysis. Results showed that as many as 78 species plants identified mostly are Fabaceae family. Habitus   majority of  the plants are in the form of  trees (42%) and part of  the plant most widely used are leaves as much as 40%. Plants used for treatment of  allergies and minor injuries (29 species); increase stamina (17 species); and internal and chronic diseases (32 species).       Phytochemical analysis showed that extracts of  Alstonia scholaris bark, Homalium grandiflorum stem, Crotalaria retusa leaves, Arcangelsia flava stem, and togutil rope stem contain triterpenoid compound (malaria). Extract of toyom bark (Sterculia bongifolia) contains tannin which has the function to stop bleeding and healing of burns infections.